2016
DOI: 10.1080/02626667.2015.1036756
|View full text |Cite
|
Sign up to set email alerts
|

Point dilution tests to calculate groundwater velocity: an example in a porous aquifer in northeast Italy

Abstract: The point dilution test is a single-well technique for estimating horizontal flow velocity in the aquifer surrounding a well. The test is conducted by introducing a tracer into a well section and monitoring its decreasing concentration over time. When using a salt tracer, the method is easy and inexpensive. Traditionally, the horizontal Darcy velocity is calculated as a function of the rate of dilution and is based on the simple assumption that the decreasing tracer concentration is proportional both to the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The resulting hydrogeological configuration of the VAP is a sequence of hydrofacies typical of a distal plain, with overlapping sequences of silty‐clayed aquitards and aquicludes and fine‐grained sandy aquifers. Overall, this sedimentological setting results in a multilayered aquifer system with different degrees of confinement (Fabbri et al, 2011, 2016; Fabbri & Piccinini, 2013; Piccinini et al, 2016, 2017; Vorlicek et al, 2004). Such multilayer systems formed by sequences of low‐ and high‐permeable layers (i.e., aquitards and aquifers) are commonly found in other alluvial aquifers with elevated As concentrations, such as the lower Mekong basin (e.g., Richards et al, 2019) or Red River Floodplain, Vietnam (e.g., Postma et al, 2007).…”
Section: Site Description and Initial Conceptual Modelmentioning
confidence: 99%
“…The resulting hydrogeological configuration of the VAP is a sequence of hydrofacies typical of a distal plain, with overlapping sequences of silty‐clayed aquitards and aquicludes and fine‐grained sandy aquifers. Overall, this sedimentological setting results in a multilayered aquifer system with different degrees of confinement (Fabbri et al, 2011, 2016; Fabbri & Piccinini, 2013; Piccinini et al, 2016, 2017; Vorlicek et al, 2004). Such multilayer systems formed by sequences of low‐ and high‐permeable layers (i.e., aquitards and aquifers) are commonly found in other alluvial aquifers with elevated As concentrations, such as the lower Mekong basin (e.g., Richards et al, 2019) or Red River Floodplain, Vietnam (e.g., Postma et al, 2007).…”
Section: Site Description and Initial Conceptual Modelmentioning
confidence: 99%
“…(6), where m is the slope of the linear trend, which then allows the determination of v a with Eq. (7) (Piccinini et al 2016):…”
Section: Permeable Injection Bag Methodsmentioning
confidence: 99%
“…As an alternative to linear regression, apparent filtration velocities can also be determined using the CXTFIT code from the STANMOD software package (Šimůnek et al 1999). Piccinini et al (2016) showed, that the apparent filtration velocity can be determined by inversing the 1D advection-dispersion equation. However, instead of using concentration values normalized to C 1 , measured tracer concentrations were used as input values.…”
Section: Permeable Injection Bag Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These fine sediments often contain peat layers formed in a floodplain environment, with a thickness of decimeters and a lateral extension of kilometers. The Drainage Basin to the Venice Lagoon (DBVL) extends to the lower plain environment, alternating silty layers with low permeability and sandy permeable layers, where the primary aquifers are located (Cambruzzi et al, 2009;Dal Prà et al, 1992;Fabbri and Piccinini, 2013;Fabbri et al, 2011Fabbri et al, , 2016Piccinini et al, 2015Piccinini et al, , 2016Vorlicek et al, 2004) (Fig. 1C).…”
Section: Geological and Hydrogeological Settingsmentioning
confidence: 96%